Safety and/or hazard near miss reporting in an international energy company - LEVA, MARIA CHIARA (My University, 2011)
This paper presents the preliminary progress of an industry driven programme to improve the data monitoring of safety/hazard near miss reporting from front line staff of a branch of a multinational energy supply company in Ireland. The paper discusses the main factors that emerged as possible causes for underreporting and the course of action selected for addressing them. The initiative, which is only in operation for 4 months has already led to an increase in reporting of ?near misses? by a factor of nine. Furthermore, the level and detail of the reports is far greater than had previously being received.
PUBLISHED
Keywords: Environmental Safety; Reporting